(untitled) (Global Journal of Management and Business Research, 2022)
The present study estimates the impact of financial development and resource rents on total factor productivity in Gulf countries We used the panel data from 1984 to 2019 and applied the GMM approach The results indicate that financial development and resource rents affect total factor productivity positively in Gulf Cooperation Council GCC countries The present study used population corruption and trade openness as control variables the results indicate that increasing trade openness contributes positively to total factor productivity However increasing corruption and population deteriorate productivity